2011
DOI: 10.1074/jbc.m111.236711
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of p21Cip1 through Anaphase-promoting Complex/Cyclosome and Its Activator Cdc20 (APC/CCdc20) Ubiquitin Ligase Complex-mediated Ubiquitylation Is Inhibited by Cyclin-dependent Kinase 2 in Cardiomyocytes

Abstract: Background: p21Cip1 is controlled by both a transcriptional and post-translational mechanism during cell cycle progression and differentiation. Results: CDK2 blocks APC/C Cdc20 -mediated ubiquitylation of p21 at the N terminus, causing G 2 arrest in mitogen-stimulated cardiomyocytes. Conclusion:The regulation of p21 ubiquitylation is required to maintain a terminal differentiation state of cardiomyocytes.Significance: This provides a novel insight on the control of cell cycle arrest in terminal differentiation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…These observations suggest that dephosphorylation of p21 is the pre-requisite for its ubiquitination. More importantly, the interaction between Cdk2 and p21 has been shown to inhibit the APC/C Cdc20 -mediated degradation of p21 during G2/M progression [46]. These findings further supports our hypothesis that p21 is dephosphorylated as the cell exit mitosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These observations suggest that dephosphorylation of p21 is the pre-requisite for its ubiquitination. More importantly, the interaction between Cdk2 and p21 has been shown to inhibit the APC/C Cdc20 -mediated degradation of p21 during G2/M progression [46]. These findings further supports our hypothesis that p21 is dephosphorylated as the cell exit mitosis.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we found that p21 accumulated rapidly in Bat3 -KD cells released from a nocodazole arrest, whereas the phosphorylation of p21 was reduced. Degradation of p21 by APC/C Cdc20 during G2/M progression has also been reported to occur during prometaphase and the interaction between Cdk2 and p21 inhibits this process [17] , [46] . These findings suggest that the decreased p21 phosphorylation in the Bat3 -KD cells results in continuous p21 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] In prometaphase, p21 is recognized at its D-box motif by APC/C Cdc20 when bound to Cdk1/cyclin B, 65 which is counteracted by the overexpression of Cdk2, at least in cardiomyocytes. 67 Interestingly, Skp2 silencing induces a slight accumulation of p21 probably representing another degradation pathway of p21 during mitosis. 65 Recently, it has been shown that a fourth E3 ligase CRL2 LRR1 (Cullin 2-RING ubiquitin ligase/leucinerich repeat protein) is acting only and specialized in the cytoplasm.…”
Section: Phosphorylationmentioning
confidence: 99%
“…40) CDK2 was shown to suppress the interaction of p21 with CDC20 and facilitate the degradation of p21, thus regulating mitosis. [41][42][43] KRAS is a member of the p21 small GTPase family and numerous investigations have reported that the overexpression of p21 proteins encoded by KRAS was detected in the cardiovascular disease. [44][45][46] As reported previously, polymorphisms in estrogen receptor (ER)-α were correlated with increased risk of MI, and the activation of ER-α was regulated by p21-activated kinase 1.…”
Section: Discussionmentioning
confidence: 99%